Orienting Asean Towards Its People: Enabling Engagement With Local NGOs - Rahman, Serina (2016)
Non-governmental organisations (NGOs), civil-society organisations and grassroots groups are a growing phenomenon across Southeast Asia. Many of these organisations fill in gaps and provide services that are not otherwise met by local authorities and governments; others purport to be the voice of the marginalised, disempowered or discriminated. There is a broad spectrum of these organisations present in Southeast Asia – from the home-grown entity that scavenges funds from myriad sources and volunteers; to large, international establishments with substantial regular funding, full-time staff and transnational networks and influence. ASEAN’s history in dealing with NGOs is chequered. Most affiliated organisations are government-owned or government-influenced organisations (GONGOs) who support ASEAN’s goals and legitimise its policies. This paper proposes that ASEAN should be more supportive of local ground-up organisations so that the regional body can act upon its goal of nurturing caring, equitable and inclusive communities with an empowered civil society, as well as fulfil its commitment to achieving the UN’s Sustainable Development Goals. An NGO Matrix that can be used as a tool to plot organisation types could help identify groups that should get the most support. As a demonstrative example, the tool has been applied to several environmental organisations currently active in South Malaysia.